Data professionals’ attitudes on data privacy, sharing, and consent in healthcare and research - Katya Kaplow; Max Downey; Darren Stewart; Allan B. Massie; Jennifer D. Motter; Lauren Taylor; John Massarelli; Taylor Matalon; Carolyn Sidoti; Macey L. Levan; Brendan Parent (Digital Health, 2024)
Objective Individuals who work on health data systems and services are uniquely positioned to understand the risks of health data collection and use. We designed and conducted a survey assessing the perceptions of those who work with health data around health data consent, sharing, and privacy practices in healthcare and clinical research. Methods A 43-item online survey was distributed via a market research firm to individuals (18+) who work with health data in the United States from March to April 2023. Descriptive statistics were calculated for all variables. Associations with demographic variables were assessed using Pearson's X 2 tests and ordinal logistic regression. Results Most of our respondents (61.7%) reported that they would trust people to use their health data across various sectors, but more respondents trusted those working in academic medical research (86.5%) and healthcare offices (89.9%) compared to those working in industry (68.2%). Despite this reported trust, a strong majority believed that individuals should have complete control over their health data (97.3%), specific consent should be obtained for each use of their health data (92.0%), and that there should be higher standards of consent and privacy for health records data than other types of data (93.7%). Conclusions Based on our findings, we might infer that people who work with health data generally trust institutions across sectors to protect their health data. However, many would prefer to have complete control over who has access to their health data and how it is used. These insights should be explored further through qualitative studies.